THE EFFECT OF JIGSAW AND PAIR SWITCH PATRNER PRESENT ON THE HIGH AND LOW MOTIVATED STUDENTSâ VOCABULARY MASTERY - Fakhruddin, Afief; Yuliasri, Issy; Linggar Bharati, Dwi Anggani (English Education Journal, 2013)
This study is investigated the effect of jigsaw and pair switch partner present on the high and low motivated studentsâ vocabulary mastery. The statement of problems were (1) How significant is the vocabulary mastery if high motivated students were treated with jigsaw, (2) How significant is the vocabulary mastery if high motivated students were treated with pair switch partner presents, (3) How significant is the vocabulary mastery if low motivated students were treated with jigsaw, (4) How significant is the vocabulary mastery if low motivated students were treated with pair switch partner presents, (5) How significant is the vocabulary mastery if high and low motivated students were treated with jigsaw, (6) How significant is the vocabulary mastery if high and low motivated students were tratedwith pair switch partner presents, (7) Is there any interaction between vocabulary mastery, strategy, and students motivation. This study was exprimental factorial design. This study used test, questionnaire and observation. The result showed that all results were not significants, and only pair switch partner present gave effect to the high motivated students and there was not interaction between vocabulary mastery, strategy, and students motivation.Â  It can be concluded that the strategy were not effective.